Measures of Agreement Between Computation Programs and Experiment: The Case of Beams with Circular Cuts in their Webs - Khouadjia, Mohamed Lyes Kamel; Temami, Oussama; Kessal, Oussama; Belkadi, Ahmed Abderraouf (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the field of metal construction, cellular beams represent an attractive solution to meeting the various technical and economic constraints, especially for large-span buildings. In particular, they allow components linked to the construction to pass through their openings (ventilation ducts, electrical threads, etc.) and thus contribute to significantly reducing the thickness of the floors.
Keywords: cellular beam; circular cut; openings; load location; metal construction; inflexion-EF; belka ażurowa; cięcia kołowe; obciążenia; konstrukcje metalowe